Achieving Sustainable Community Development - Helping Build Appropriate and Resilient Community Governance Structures (The Australasian Institute of Mining and Metallurgy, 2009)
This paper talks about the experiences of groups we have worked with over the last few years in the Asia-Pacific region (Australia, Canada, New Zealand and Papua New Guinea) and the ways that they have worked to bridge the divide between traditional and introduced structures, governance at a regional level and the introduction of traditional values into monitoring and evaluation practices. In doing this these groups have created structures and processes which have helped them engage both more effectively with external stakeholders while maintaining the legitimacy of their own operations with their own constituents. These are important ideas for those involved in the mining industry that could provide a number of very tangible benefits to mining firms and their engagement with these kinds of groups.